The effect of the modulation transfer function on the image in an acoustic microscope - LITNIEWSKI, Jerzy (Archives of Acoustics, 1983)
This paper considers the effect of the diffraction phenomenon and of errors in the geometry of the system on the quality of images obtained using a scanning acoustic microscope working in transmission. An analysis of image formation is presented, permitting the derivation of the formula for the modulation transfer function (MTF). The effect of nonaxial and out-of-parallel elements of the system on the symmetry of this function with respect to zero frequency is determined. The paper also shows microscopic images obtained from numerical simulation for two selected objects with different magnitude of deviation from the symmetry of the function MTF. The shape of the function MTF for a system working at a relatively low frequency of 3 MHz was also determined experimentally and compared with the shape expected according to the theoretical formula derived in this paper. Satisfactory agreement was observed.